Household food security in rural Tamil Nadu: a survey from Kaniyambadi block, Vellore district - Kailasam, Abirami; Kannan, Bharathi; Lochan, Eashwar Barath; K., Sathya Narayanan; Chaudhuri, Sirshendu; Mohan, Venkata Raghava (International Journal Of Community Medicine And Public Health, 2019)
Background: Adequate and safe food is a basic requirement for every individual. Inadequate food leads to food insecurity. Household-level food insecurity may directly influence the health of an individual. We aimed to assess the prevalence of household-level food insecurity in the rural areas of Kaniyambadi block and to assess the household level determinants of food insecurity. Methods: A cross-sectional study was conducted in villages of Kaniyambadi block, a rural development block of Vellore district in Tamil Nadu. Households were the unit of study. The interview was conducted with a pre-tested, semi-structured questionnaire in Tamil. ‘U.S. Food Security Survey module’, September 2012, for a reference period of 30 days was used to determine food security status. Results: One hundred and fifty households were selected; 15 from each 10 randomly selected villages. Prevalence of food insecurity we got as 52.7% [95% CI: 44.6%, 60.8%]. Determinants like ‘low (<1225 INR/ month) per capita income’ [Adjusted odds ratio (AOR)- 6.7; 95% CI: 3.3,13.6]; ‘presence of debt at the time of interview’ [AOR- 3.5; 95% CI:1.7, 7.3] and ‘presence of at least one smoker in the family’ [AOR- 3.2; 95% CI:1.5, 6.8], were found to be associated significantly with food insecurity, after adjusting for the clusters by multi-level modelling. Conclusions: Food insecurity is a hidden phenomenon in India. Poverty is the key determinant behind this. To alleviate food insecurity, it will be logical to adopt multi-dimensional approaches with thrust on implementing the existing poverty alleviating programs.